1H NMR for quantifying sulfide trapping efficiency by using 1, 3, 5‐tris(2‐hydroxyethyl)‐1, 3, 5‐triazinane. (11th April 2014) - Canuto, André V. S.; Echevarria, Aurea
<x xml:space="preserve">Abstract</x> Hydrogen sulfide (H2S) is an extremely toxic colourless gas; it is corrosive and denser than air. It usually happens in oil and natural gas fields, refineries, coal mines, and in some industrial effluent treatment systems. This work presents an alternative method of monitoring and quantifying H2S trapping efficiency by using 1, 3, 5‐tris(2‐hydroxyethyl)‐1, 3, 5‐triazinane as a sequestering agent, and sodium sulfide as a source of sulfide ion, through 1H NMR spectroscopy. The results proved that the reaction occurs very quickly at 20 °C at pH 7 and 10. 3, 5‐di(2‐hydroxyethyl)‐1, 3, 5‐thiodiazinane and 5‐(2‐hydroxyethyl)‐1, 3, 5‐dithiozinane were observed and quantified; it was evidenced that 1H NMR spectroscopy can be applied as a fast and effective method to quantify H2S trapping efficiency. Copyright © 2014 John Wiley & Sons, Ltd.